Enabling diverse learners to thrive in the online homiletics classroom - Lamb, Lisa (Teaching theology and religion, 2019)
Many early efforts at teaching preaching online incurred disastrous losses in quality. Revamped versions now claim to meet, and in some areas even exceed, classroom learning effectiveness, with potentially significant gains for students from non-dominant cultures. Students preach in local ethnic and denominational contexts, so a wider range of sermon styles can flourish in indigenous soil. Students hear immediate feedback from their community, and from their online peers and professor. Online discussion formats level the playing field for non-native speakers. By remaining embedded in their denominational and ethnic environments, student's cultural differences may be simultaneously affirmed and critiqued. This article describes capacities which predict success among preaching students, and how culture may influence the manifestation of these capacities. It details best practices and continuing challenges for professors making the transition to online preaching courses, as they seek to build culturally sustaining learning environments in which diverse students may flourish.